Implementation of a TSMCSPO Controller on a 3-DOF Hydraulic Manipulator for Position Tracking and Sensor-Less Force Estimation - Karam Dad Kallu; Saad Jamshed Abbasi; Hamza Khan; Jie Wang; Min Cheol Lee (IEEE Access, 2019)
In this study, a three-degree-of-freedom hydraulic system device configured as a master-and-slave manipulator system is considered. A methodology to estimate reaction force in aforementioned system is proposed without utilizing any force sensor/signal. A terminal sliding control with a sliding perturbation observer (TSMCSPO) is designed for coupled master-slave system. The fundamental benefit of the proposed scheme is that the sliding perturbation observer estimates the reaction force related to the end effector and second link without utilizing a force sensor. Robust and accurate position tracking is achieved with terminal sliding-mode control in addition to control of the slave manipulator. The position and force tracking for master-slave is estimated based upon bilateral control strategy. The difference in the reaction and operating force is included in the impedance model. The impedance model is implemented in the master device to provide the operator with a sense of the reaction force when it connects with the environment. The experimental results confirm the robust position and force tracking of the slave manipulator.